The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11094-011-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antimicrobial activity of 2-aroylmethylene-6-hydroxy-2,3-dihydroindol-3-ones

Abstract: The interaction of methyl esters of aroylpyruvic acids with 2-aminophenol was used to form 2-aroylmethylene-6-hydroxy-2,3-dihydroindol-3-ones. The structures of these compounds were verified by IR and 1 H NMR spectroscopy; the antimicrobial activity of the compounds synthesized here was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The reaction in polar aprotic solvents, such as DMSO and DMF, was also tested. It was found that the outcome of these reactions also improves in the presence of water, but the overall performance in these solvents remains relatively poor (entries [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction in polar aprotic solvents, such as DMSO and DMF, was also tested. It was found that the outcome of these reactions also improves in the presence of water, but the overall performance in these solvents remains relatively poor (entries [10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…1). [10][11][12][13][14][15][16][17] Normally, preparation of such compounds relies heavily on the chemistry of isatins, which makes synthetic approaches to certain substitution patterns hardly accessible. An alternative synthetic platform for assembling indoline alkaloids and related non-natural, biologically active target molecules has also emerged, relying on the chemistry of 2alkylidene-3-oxindoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 7 2-Alkylideneindolin-3-one derivatives bearing a single indoline moiety or two remotely positioned indoline subunits are found in nature and are endowed with important biological activities as well. 8 15 2-Alkylideneindolin-3-ones bearing a conjugated nitrile function (i.e., 2-(3-oxoindolin-2-ylidene)acetonitriles 1 ) were used as advanced precursors in the synthesis of pyridazino[4,3- b ]indoles 2 , which possess strong inhibitory activity against Mycobacterium tuberculosis ( Scheme 1 ). 16 Recently, we have communicated on the unexpected formation of 2-alkylideneindolin-3-ones taking place upon treatment of ortho -nitrochalcones with potassium cyanide and acetic acid in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are relatively rare and have been far less studied with respect to their biological activity or cycloaddition chemistry as compared to the 2-oxindole isomers. Moreover, current methods for generating these compounds are rather limited and generally low yielding . We therefore investigated a two-step displacement-decarboxylation sequence toward these products, and our results are summarized in Scheme .…”
mentioning
confidence: 99%